Comparative analysis of meat and fat tissue of Mangalica and meat-type hybrid pigs by means of Computerised Tomography - Koncz, A.; Petrási, Zsolt; Romvári, Róbert; Donkó, Tamás; Garamvölgyi, Rita; Repa, Imre (Acta Agraria Kaposváriensis, 2014)
The tissue composition of 6-6 Mangalica and meat-type pigs was determined by serial in vivo CT scanning. X-ray density frequency curves were developed from the whole body to determine the different tissue volumes. The calculated meat to fat ratio values were 3.4, 3.2 and 1.9 (meat-type pigs), while those of fat-type pigs were 1.0, 0.6 and 0.5, respectively, in the average weight of 30, 60 and 90 kg. In these weights, the meat percentage values were 35.5, 30.9 and 28.5 of the Mangalicas and 61.5, 57.7 and 53.2 % of meat-type pigs. The investigation of the tissue development in the body was carried out by means of 3D histograms. In the cross-sectional images the surface of the m. longissimus dorsi and also the m. semitendinosus was determined and the fat thickness at the back and the rump were measured. The intramuscular fat content was characterised by the average X-ray density value.
Keywords: Pig; meat-type; Mangalica; tissue composition; computerized tomography